THE INFLUENCE OF PROMOTION AND SERVICE QUALITY TOWARD CONSUMER PURCHASE DECISIONS OF LESTARI JAYA BROILERS CHICKEN STORE - Mustopa, Aji; Mahendra, Febriyansyah; Arantza, Oxa De; Putra, Aldi Ardana; R, Rifqi Muhammad Hafizh; Hendri, Meriza (CENTRAL ASIA AND THE CAUCASUS, 2022)
Bandung City has large consumption of broiler chickens and based on reporting from Central Statistics Agency, consumption was 728,968 of broiler chickens in 2019. Lestari Jaya is a shops that sell boiler chicken in Bandung. Unfortunately, there was a decline of selling that can be seen from data from January to June 2020 period before the pandemic as many as 38,494 broiler chickens, and the same period in 2021 only 23,137 broiler chickens. There was a decrease 15,357 broiler chickens or 39.89%. The purposes of this study were to know and analyze promotion, service quality, purchase decision and the influence of promotion toward purchasing decisions and the influence of service quality toward purchase decisions. Quantitative methods with descriptive and verificative approaches were used to answer the research questions. Data were collected from 97 respondents. The results showed that information and knowledge about promotion is still not understood. The quality of service that has been carried out is very good. The promotion variable had no significant influence toward purchasing decisions, while the service quality variable had a significant influence toward purchasing decisions.